Residency program in nursing obstetrical: reflections from the experience of residents - Thamiza Laureany da Rosa dos Reis; Jacqueline Silveira de Quadros (Universidade Federal de Santa Maria, 2017)
Aim: to report the implementation of the National Residency Program in Obstetrical Nursing from the perspective of the obstetrical nurses who graduated in the first class of the southern region of Brazil. Method: report of experience. The training scenarios of obstetrical nurses are represented by a public maternity unit, a Basic Health Unit and two Family Health Strategies. Results: many advances have been achieved through joint discussions and exchanges of knowledge among all actors involved in the program implementation process. Currently, teamwork, discussion of behaviors and prescriptions, and trust in the work of the residents are possible. Final considerations: the Residency Program in Obstetric Nursing is in the process of being implemented and, therefore, new challenges arise, and, in some cases, limitations and difficulties also arise, which contribute to its improvement and reorients the qualification actions of nurses Obstetricians